Especificaciones de cálculo de la vida útil y estado límite de corrosión - Andrade, C. (Revista ALCONPAT, 2013)
Estimates of service life of concrete structures are rapidly moving from laboratories to the standards and to be specified in the construction for large infrastructures. So service life of 100 years or more were required to Oresund bridge or the new Panama Canal. However, the specification is made without defining how to prove the specified durability and in some cases, without even mentioning the tests and limit values to be used. Present communication describes the most important aspects to be specified in the chloride prediction models in addition to the diffusion coefficients, which are the surface concentration, the aging factor, the limit of chlorides and the acceptable probability of corrosion.